مدى ادارك أهمية قياس جودة الخدمات الصحية في المؤسسات العمومية الاستشفائية في الجزائر دراسة مقارنة بين فئة العاملين وبين المستشفيات - ‫تيقاوي, ‫العربي‬ ‬ (Recherches économiques et managériales; No 22 (2017): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES(Décembre), 2018)
تهدف هذه الدراسة إلى التعرف على مدى ادارك أهمية جودة الخدمات الصحية في المؤسسات العمومية الاستشفائية في الجزائر وقياسها من منظور العاملين بالمستشفيات المبحوثة، ولتحقيق ذلك تم صياغة فرضيات ولاختبار صحتها قام الباحث بتصميم استبانة كأداة لجمع البيانات من أفراد العينة المبحوثة وتحليلها، وتوصلت إلى وجود فروقات حسب آراء العاملين وحسب المستشفيات المبحوثة حول إدراك أهمية جودة الخدمة الصحية، باستثناء بعد الاعتمادية الذي دل على عدم وجود فروقات بين آراء العينة المبحوثة، وتوصي الدراسة بضرورة العمل على تحسين نوعية الأجهزة والأدوات الطبية المطلوبة وتوفير المحيط العملي المناسب ليتمكن الإفراد العاملين من تقديم أفضل خدماتهم والدراسة عن كفاءات طبية . الكلمات الدالة : الجودة، الخدمات الصحية، جودة الخدمات الصحية . Abstract :        The aim of this study is to identify the importance of the quality of health services in public hospitals in Algeria and to measure them from the perspective of the employees of the hospitals in question. In order to achieve this, hypotheses were prepared and tested for validity. The researcher designed a questionnaire as a tool for collecting and analyzing data from the surveyed individuals, The opinion of the employees according to the hospitals investigated about the importance of the quality of health service, except after the reliability of the absence of any differences between the views of the sample and the study recommends the need to work to improve the quality of medical devices and tools required and Providing the appropriate working environment so that the personnel can provide their best services and study medical competencies . Key words : quality, health service, quality of health service.